Nanowire array composed of ferrocobalt-based heterostructures, preparation method and application

By growing CoFe-LDH on foam nickel substrate and converting it into Co9S8-Fe3O4/VNF composite material, forming a cobalt-iron-based heterostructure nanowire array, the problems of low efficiency and high cost of existing OER catalysts are solved, and the problem of low efficiency and high cost of existing OER catalysts is achieved. Low overpotential and efficient OER performance and stability at high current density reduce the energy barrier for hydrolysis.

CN119307965APending Publication Date: 2025-01-14JILIN UNIVERSITY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411429523.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing OER catalysts are inefficient and costly in water decomposition, especially the scarcity and high cost of ruthenium-based materials limit the development of electrocatalytic water decomposition, and the electron conductivity of Co9S8 is poor and has few active sites, which cannot meet the industry. Requirements for alkaline electrolysis of grade large currents.

Method used

CoFe-LDH nanosheets were grown on a foam nickel substrate by hydrothermal method and converted into Co9S8-Fe3O4/VNF composite in a muffle furnace to form a nanowire array composed of cobalt-iron-based heterostructure to optimize the OER middle The adsorption strength and electron structure of the body improve the active surface area and ion/electron transfer rate.

Benefits of technology

Achieve high-efficiency OER performance with ultra-low overpotential under large current density, low Tafel slope, small impedance, large active area, and stable under alkaline conditions, reducing the energy barrier for hydrolysis, making H and OH- Adsorption/desorption is more effective and cheap.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307965A_ABST
    Figure CN119307965A_ABST
Patent Text Reader

Abstract

The invention is suitable for the technical field of OER catalysts, and provides a preparation method of a nanowire array composed of a ferrocobalt-based heterostructure, and the preparation method comprises the following steps: pretreating a foamed nickel substrate; performing in-situ growth of a precursor CoFe-LDH nanosheet on the NF through a hydrothermal method; and synthesizing the nanowire array composed of the ferrocobalt-based heterostructure: putting a precursor into a muffle furnace, heating, keeping the temperature so that the precursor is thoroughly converted into a Co-Fe-O intermediate, immersing NF on which the intermediate grows into a polytetrafluoroethylene reaction kettle lining, carrying out a hydrothermal reaction, and naturally cooling to the room temperature to obtain a Co9S8-Fe3O4 / VNF composite material (the vulcanized NF is abbreviated as VNF), so that the nanowire array composed of the ferrocobalt-based heterostructure and the Co9S8-Fe3O4 / VNF composite material is obtained. The nanowire array is composed of a ferrocobalt-based heterostructure. The invention further provides a nanowire array composed of the ferrocobalt-based heterostructure and application of the nanowire array in preparation of a working electrode of an oxygen evolution reaction catalyst. According to the heterostructure catalyst provided by the invention, the adsorption strength of an OER intermediate can be optimized to realize high intrinsic OER activity, and efficient and stable water decomposition is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of OER catalysts, and in particular relates to a nanowire array composed of a cobalt-iron-based heterostructure, a preparation method and an application thereof. Background Art

[0002] Hydrogen is considered to be one of the ideal energy carriers because of its special energy density and its non-toxicity and pollution-free nature. Electrocatalytic water splitting is an environmentally friendly, efficient and sustainable method for hydrogen production, among which alkaline electrolysis technology is particularly mature. Electrocatalytic water splitting can be divided into two different chemical reactions: anode hydrogen evolution reaction (HER) and cathode oxygen evolution reaction (OER). OER has a multi-step electron transfer process and requires higher energy than HER, which greatly limits the efficiency of electrocatalytic water splitting. Therefore, an OER electrocatalyst that can improve efficiency is needed. At present, the first choice for commercial OER electrocatalysts is still ruthenium-based materials, but their development in water splitting is hindered by scarcity and high cost. Therefore, it is crucial to develop efficient and stable OER catalysts.

[0003] Among transition metal-based OER catalysts, Co-based catalysts have attracted widespread attention due to their high OER performance, cost-effectiveness, and structural versatility. Cobalt-based compounds, such as oxides, sulfides, phosphides, and their composites, have gradually become potential catalysts for high current density water splitting OER. Among them, Co9S8 with platinum-like crystal planes has gradually attracted attention because of its low cost, good redox ability, and unique lattice arrangement (universal Co tetrahedrons and octahedrons coexist in cubic cells). However, single Co9S8 has poor electronic conductivity, a small number of active sites, and weak adsorption energy for OER intermediates, which cannot achieve high efficiency and stability, let alone meet the requirements of industrial-grade high-current alkaline electrolysis. To solve this problem, it is urgent to develop new catalyst materials and optimize the adsorption strength of OER intermediates to achieve high intrinsic OER activity, thereby achieving efficient and stable water splitting. Summary of the invention

[0004] The purpose of the embodiments of the present invention is to provide a method for preparing a nanowire array composed of a cobalt-iron-based heterostructure, aiming to solve the problems existing in the above-mentioned background technology.

[0005] The embodiment of the present invention is implemented as follows: a method for preparing a nanowire array composed of a cobalt-iron-based heterostructure comprises the following steps:

[0006] S1, pre-treating the nickel foam substrate: removing surface impurities from the nickel foam substrate NF and then drying it;

[0007] S2. In situ growth of precursor CoFe-LDH nanosheets on NF by hydrothermal method: Co(NO3)2·6H2O, Fe(NO3)3·9H2O, urea and NH4F were dissolved in deionized water, and a pink clear solution was obtained after stirring. The clear solution and the treated nickel foam substrate were transferred to a polytetrafluoroethylene reactor liner for hydrothermal reaction. After naturally cooling to room temperature, the obtained product was washed and vacuum dried overnight to obtain a precursor.

[0008] S3. Synthesis of nanowire arrays composed of cobalt-iron-based heterostructures: Place the precursor in a muffle furnace, heat it up and maintain it to completely convert the precursor into a Co-Fe-O intermediate, immerse the NF with the intermediate into the inner lining of a polytetrafluoroethylene reactor filled with a sodium sulfide solution, and perform a hydrothermal reaction. After naturally cooling to room temperature, wash the obtained product and vacuum dry it overnight to obtain a Co9S8-Fe3O4 / VNF composite material, i.e., a nanowire array composed of a cobalt-iron-based heterostructure.

[0009] Preferably, in S1, the step of removing surface impurities from the nickel foam substrate is specifically: ultrasonically treating the nickel foam substrate in acetone solution, anhydrous ethanol and deionized water for 10 min several times, and then ultrasonically treating the nickel foam substrate in 1.0 M HCl solution, deionized water and anhydrous ethanol for 10 min respectively.

[0010] Preferably, in S2, the molar ratio of Co(NO3)2·6H2O, Fe(NO3)3·9H2O, urea and NH4F is 1-5:0.5-5:2-10:2-10.

[0011] Preferably, in S2, the temperature of the hydrothermal reaction is 100-200°C and the time is 4-12h.

[0012] Preferably, in S3, the heating rate of the heating step after heating and maintaining is 3-10°C min -1 , heat to 200-500℃ and maintain for 1-10h.

[0013] Preferably, in S3, the concentration of the sodium sulfide solution is 0.01-0.1 mmol / mL.

[0014] Preferably, in S3, the temperature of the hydrothermal reaction is 100-200° C., and the time is 2-12 h.

[0015] Another object of the embodiment of the present invention is to provide a nanowire array composed of a cobalt-iron-based heterostructure, which is prepared by the above preparation method.

[0016] Another object of the embodiments of the present invention is to provide an application of a nanowire array composed of a cobalt-iron-based heterostructure in preparing a working electrode for an oxygen evolution reaction catalyst.

[0017] The nanowire array composed of the cobalt-iron-based heterostructure provided in the embodiment of the present invention can be used as a heterostructure catalyst. Due to the modification of the interfacial atomic coordination environment and electron exchange between different components, the electronic structure of the active site can be effectively adjusted, thereby optimizing the adsorption strength of the OER intermediate to achieve high intrinsic OER activity, which can increase the active surface area and enhance the rate of ion / electron transfer; Fe3O4 and Co9S8 are combined into nanowires composed of heterojunctions, which can achieve kinetically decoupled adsorption / dissociation of hydroxyl / water while having a very large specific surface area, thereby promoting OER on the heterogeneous interface. At the same time, the metallic conductivity of Co9S8-Fe3O4 enables electrons to be efficiently transferred and transmitted on the catalyst and catalyst / electrolyte interface, which produces a rich oxide / sulfide interface, providing a more accessible catalytic center and a more diffuse channel for rapid gas escape, while reducing the energy barrier for water dissociation, allowing *H and OH to react. - The adsorption / desorption of (OH*) is more effective;

[0018] In the embodiment of the present invention, CoFe-LDH is used as a sacrificial template, and the Co9S8-Fe3O4 / VNF heterojunction electrocatalyst formed by calcination and sulfurization achieves high-efficiency OER performance with ultra-low overpotential at a high current density. The constructed Co9S8-Fe3O4 / VNF heterojunction electrocatalyst is arranged quasi-vertically on the entire substrate surface as a high-density nanowire. This structure with a large number of gaps enables it to have a larger active area and more exposed active sites. Under alkaline conditions, only low overpotentials of 229mV and 301mV are required to achieve 100mA cm -2 and 1000mA cm -2 The OER process at this current density shows a Tafel slope as low as 31.46 mV dec -1 , has a small impedance and a large active area and can maintain stable operation for more than 100 hours at a high current density. At the same time, the preparation process is simple, the raw materials are abundant, and the cost is low. It provides a convenient and concise strategy for the preparation and design of high current density transition metal-based OER catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The XRD spectrum of the Co9S8-Fe3O4 / VNF composite material provided in Example 1 of the present invention;

[0020] Figure 2 This is a low-magnification SEM image of the Co9S8-Fe3O4 / VNF composite material provided in Example 1 of the present invention;

[0021] Figure 3TEM image of the Co9S8-Fe3O4 / VNF composite material provided in Example 1 of the present invention;

[0022] Figure 4 A high-resolution TEM image of the Co9S8-Fe3O4 / VNF composite material provided in Example 1 of the present invention;

[0023] Figure 5 This is the full XPS spectrum of the Co9S8-Fe3O4 / VNF composite material provided in Example 1 of the present invention;

[0024] Figure 6 The Co 2p high-resolution XPS spectrum of the Co9S8-Fe3O4 / VNF composite material provided in Example 1 of the present invention;

[0025] Figure 7 The Fe 2p high-resolution XPS spectrum of the Co9S8-Fe3O4 / VNF composite material provided in Example 1 of the present invention;

[0026] Figure 8 The O1s high-resolution XPS spectrum of the Co9S8-Fe3O4 / VNF composite material provided in Example 1 of the present invention;

[0027] Fig. 9 The S2p high-resolution XPS spectrum of the Co9S8-Fe3O4 / VNF composite material provided in Example 1 of the present invention;

[0028] Fig.10 OER polarization curves of the Co9S8-Fe3O4 / VNF composite electrode and commercial RuO2 in 1M KOH solution provided in Example 1 of the present invention;

[0029] Fig.11 The Tafel slope of the Co9S8-Fe3O4 / VNF composite electrode provided in Example 1 of the present invention and commercial RuO2 in 1M KOH solution;

[0030] Fig.12 The impedance spectra of the Co9S8-Fe3O4 / VNF composite electrode and commercial RuO2 in 1M KOH solution provided in Example 1 of the present invention;

[0031] Fig.13 CV cycle curve of Co9S8-Fe3O4 / VNF composite electrode provided in Example 1 of the present invention and its corresponding C dl ;

[0032] Fig.14 The C corresponding to the Co9S8-Fe3O4 / VNF composite electrode provided in Example 1 of the present invention dl ;

[0033] Fig.15 This is the chronopotentiometry curve of the Co9S8-Fe3O4 / VNF composite electrode provided in Example 1 of the present invention in 1M KOH solution. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0035] A nanowire array composed of a cobalt-iron-based heterostructure, the preparation method of which comprises the following steps:

[0036] S1. Pretreatment of the nickel foam substrate (NF):

[0037] NF (size 2.0×3.5cm 2 ) were ultrasonically treated in acetone solution, anhydrous ethanol and deionized water for 10 min three times, and then ultrasonically treated in 1.0 M HCl solution, deionized water and anhydrous ethanol for 10 min to remove surface impurities, and finally dried in a vacuum drying oven;

[0038] S2. In-situ growth of precursor CoFe-LDH nanosheets on NF by hydrothermal method:

[0039] Dissolve 1-5mmol Co(NO3)2·6H2O, 0.5-5mmol Fe(NO3)3·9H2O, 2-10mmol urea and 2-10mmol NH4F in 20-100mL deionized water (the molar ratio of Co(NO3)2·6H2O:Fe(NO3)3·9H2O:urea:NH4F can be 2:1:10:8, and the deionized water is 36mL). After stirring for 30 minutes, a pink clear solution is obtained. The clear solution and the pretreated NF are transferred to a 100mL polytetrafluoroethylene-lined reactor. The reactor is kept in an oven at 100-200℃ for 4-12h (specifically 120℃ for 6h). After cooling naturally to room temperature, the obtained product is washed three or four times with deionized water and anhydrous ethanol respectively, and finally vacuum dried at 60℃ overnight;

[0040] S3. Synthesis of Co9S8-Fe3O4 / VNF composite material (nanowire array composed of cobalt-iron based heterostructure):

[0041] The prepared precursor was placed in a muffle furnace at 3-10 °C min -1 The furnace is heated to 200-500℃ at a heating rate of 5℃min -1, heated to 320°C), after the heating process is completed, the temperature is maintained for 1-10h (specifically 3h) to completely convert the precursor into a Co-Fe-O intermediate, and then the NF with the intermediate is immersed in a 100mL polytetrafluoroethylene reactor lining filled with a sodium sulfide solution with a concentration of 0.01-0.1mmol / mL (specifically 0.035mmol / mL), and then heated in an oven at 100-200°C for 2-12h (specifically 180°C, 6h), and after naturally cooling to room temperature, the obtained product is washed several times with deionized water and anhydrous ethanol, and dried overnight in a vacuum at 60°C to finally obtain a Co9S8-Fe3O4 / VNF composite material (NF will be sulfurized during the reaction, and the sulfurized NF is abbreviated as VNF, and the main components are Ni3S2 and Ni).

[0042] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.

[0043] Example 1: A nanowire array composed of a cobalt-iron-based heterostructure, wherein the preparation method comprises the following steps:

[0044] S1. Pretreatment of the nickel foam substrate (NF):

[0045] The size is 2.0×3.5cm 2 The NFs were ultrasonically treated in acetone solution, anhydrous ethanol and deionized water for 10 min three times, and then ultrasonically treated in 1.0 M HCl solution, deionized water and anhydrous ethanol for 10 min respectively, and finally dried in a vacuum oven;

[0046] S2. In-situ growth of precursor CoFe-LDH nanosheets on NF by hydrothermal method:

[0047] Dissolve 1.0mmol Co(NO3)2·6H2O, 0.5mmol Fe(NO3)3·9H2O, 5.0mmol urea and 4.0mmol NH4F in 36mL deionized water, and stir for 30 minutes to obtain a pink clear solution. Transfer the above solution and a piece of pretreated NF to a 100mL polytetrafluoroethylene-lined reactor. Keep the reactor in an oven at 120℃ for 6h. After cooling naturally to room temperature, wash the obtained product with deionized water and anhydrous ethanol three or four times respectively, and finally vacuum dry it at 60℃ overnight.

[0048] S3. Synthesis of Co9S8-Fe3O4 / VNF composite material:

[0049] The prepared precursor CoFe-LDH was placed in a muffle furnace at 5 °C min -1The furnace was heated to 320° at a heating rate of 100 ℃. After the heating process was completed, the temperature was maintained at 320°C for 3 h to completely convert CoFe-LDH into Co-Fe-O intermediates. The NF with Co-Fe-O intermediates was then immersed in a 100 mL polytetrafluoroethylene reactor lining filled with a colorless solution prepared by 1.5 mmol Na2S·9H2O and 40 mL H2O, and then heated in an oven at 180°C for 6 h. After naturally cooling to room temperature, the obtained product was washed several times with deionized water and anhydrous ethanol, and dried overnight in a vacuum at 60°C to obtain the Co9S8-Fe3O4 / VNF composite material.

[0050] Performance Test:

[0051] The crystal structure of the Co9S8-Fe3O4 / VNF composite material prepared in Example 1 was analyzed by X-ray diffraction (XRD). Figure 1 As shown, in addition to VNF (mainly composed of Ni3S2 and nickel foam), the peaks of Co9S8 (JCPDS file number 02-1459) and Fe3O4 (JCPDS file number: 89-4319) coexist in the Co9S8-Fe3O4 / VNF composite material, indicating the coexistence of the two;

[0052] The morphology of Co9S8-Fe3O4 / VNF composites was analyzed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Figure 2 As shown, the SEM image shows that the nanowires are arranged quasi-vertically on the entire substrate surface as high-density nanowires. They are not aggregated but cross-linked with each other to form a three-dimensional nanowire cross-linked network structure. There are a lot of gaps in the middle of the nanowires, which is conducive to electrolyte transport and higher stability. Figure 3 TEM images confirmed that Co9S8 and Fe3O4 existed simultaneously and formed nanowires with a width of about 60nm; Figure 4 The high-resolution TEM image (HRTEM) shows clear lattice fringes with lattice spacings of 0.209 nm and 0.176 nm, corresponding to the (400) plane of Fe3O4 crystal and the (440) plane of Co9S8 crystal, respectively, further verifying the successful synthesis of Co9S8-Fe3O4 metal heterostructures;

[0053] The Co9S8-Fe3O4 / VNF composite material was analyzed by X-ray photoelectron spectroscopy, and the XPS spectrum was obtained as follows: Figure 5 As shown, it can be seen that Co, Fe, O, and S elements coexist in the Co9S8-Fe3O4 / VNF composite material; Figure 6 It can be seen that for Co9S8-Fe3O4 / VNF, Co 2p has three pairs of peaks, namely Co2+ (about 781.3 and 796.7 eV), Co 3+ (about 778.7 and 794.1 eV) and satellite peaks; according to Figure 7 It can be seen that Fe 2p also has three pairs of peaks, namely Fe 2+ (about 710.8 and 724.0 eV), Fe 3+ (about 713.3 and 726.9 eV) and satellite peaks; according to Figure 8 It can be seen that O 1s has chemical adsorption O ad , M-OH and MO characteristic peaks; according to Fig. 9 It can be seen that S2p has two peaks. In addition to the MS peak, there is also a satellite peak, most of which comes from the SO bond in sulfate, indicating that sodium sulfide not only provides S 2- , and also exhibits reducing properties, converting some trivalent elements into divalent elements.

[0054] The Co9S8-Fe3O4 / VNF composite material prepared in Example 1 was used as a catalyst for electrochemical testing, including the following steps:

[0055] (1) The Co9S8-Fe3O4 / VNF composite material prepared in Example 1 was cut into a size of 0.3 cm×1.2 cm and used as a working electrode for the oxygen evolution reaction catalyst, denoted as Co9S8-Fe3O4 / VNF electrode:

[0056] Commercial RuO2 powder was dissolved in a mixed solution of 960 μL deionized water and 40 μL naphthol, and after ultrasonication for 30 min, the powder was evenly dripped on the nickel foam and dried at room temperature to obtain a catalyst-loaded working electrode as a comparative example;

[0057] (2) The electrochemical test was carried out in a standard three-electrode test system, using the two electrodes prepared in step (1) as working electrodes, a saturated calomel electrode as a reference electrode, a carbon rod as a counter electrode, and a 1 M KOH solution as an electrolyte. The electrochemical test was carried out in an alkaline solution (1 M KOH pH = 13.6) at room temperature (25° C.) on a CHI660B electrochemical workstation;

[0058] (3) At a scan rate of 2 mV s -1 The LSV curves of the OER process were measured under the conditions of different scan rates (10, 20, 30, 40 and 50 mV s -1 ) to characterize the double-layer capacitance of ECSA, that is, through C dl The size of the active area is used to illustrate the size of the active area. When recording the EIS spectrum, the frequency range is 10 5 Up to 10 -2HZ (amplitude of 10 mV), for the OER stability test, the current density was kept at 1000 mA cm by chronopotentiometry -2 Under these conditions, the change of potential over time was recorded;

[0059] The three-electrode system with the homemade catalyst as the anode was used to study the electrocatalytic OER behavior of the prepared samples in 1M KOH solution in detail. Under standard conditions, the thermodynamic equilibrium potential of OER is 1.23V, but in the actual reaction process, there are unfavorable kinetic factors that hinder the reaction, and an additional potential is required, namely the overpotential. The overpotential refers to the difference between the electrode potential and the standard electrode potential (1.23V). The smaller the overpotential, the smaller the OER reaction resistance and the better the catalyst performance. Fig.10 It can be seen that at a current density of 100 mA cm -2 and 1000mA cm -2 When the overpotential of Co9S8-Fe3O4 / VNF electrode is only 229mV and 301mV, both are much smaller than the overpotential of commercial RuO2. Fig.11 It can be seen that the Co9S8-Fe3O4 / VNF electrode not only has a lower overpotential, but also has the lowest Tafel slope of only 31.46 mV dec. -1 ;like Figures 12 to 14 As shown in Figure 2, the Co9S8-Fe3O4 / VNF electrode exhibits lower impedance and higher active area; Fig.15 As shown, at 1000mA cm -2 The chronopotentiometry test was carried out for 100 h at the current density, and the Co9S8-Fe3O4 / VNF electrode showed excellent stability without obvious decline;

[0060] In summary, the nanowires composed of Co9S8-Fe3O4 heterojunctions formed by calcination and sulfidation using CoFe-LDH as a sacrificial template prepared in the embodiment of the present invention can not only maximize the conductivity, charge transfer rate, ECSA and active site density of the catalyst, but also regulate the electron distribution and enhance the reaction kinetics, thereby achieving excellent OER performance at high current density and good durability.

[0061] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a nanowire array composed of a cobalt-iron-based heterostructure, characterized in that: The following steps are involved: S1, pre-treating the nickel foam substrate: removing surface impurities from the nickel foam substrate NF and then drying it; S2. In situ growth of precursor CoFe-LDH nanosheets on NF by hydrothermal method: Co(NO3)2·6H2O, Fe(NO3)3·9H2O, urea and NH4F were dissolved in deionized water, and a pink clear solution was obtained after stirring. The clear solution and the treated nickel foam substrate were transferred to a polytetrafluoroethylene reactor liner for hydrothermal reaction. After naturally cooling to room temperature, the obtained product was washed and vacuum dried overnight to obtain a precursor. S3. Synthesis of nanowire arrays composed of cobalt-iron-based heterostructures: Place the precursor in a muffle furnace, heat it up and maintain it to completely convert the precursor into a Co-Fe-O intermediate, immerse the NF with the intermediate into the inner lining of a polytetrafluoroethylene reactor filled with a sodium sulfide solution, and perform a hydrothermal reaction. After naturally cooling to room temperature, wash the obtained product and vacuum dry it overnight to obtain a Co9S8-Fe3O4 / VNF composite material, i.e., a nanowire array composed of a cobalt-iron-based heterostructure.

2. The method for preparing a nanowire array composed of a cobalt-iron-based heterostructure according to claim 1, characterized in that: In S1, the step of removing surface impurities from the nickel foam substrate is specifically as follows: ultrasonically treating the nickel foam substrate in acetone solution, anhydrous ethanol and deionized water for 10 minutes several times, and then ultrasonically treating the nickel foam substrate in 1.0M HCl solution, deionized water and anhydrous ethanol for 10 minutes respectively.

3. The method for preparing a nanowire array composed of a cobalt-iron-based heterostructure according to claim 1, characterized in that: In S2, the molar ratio of Co(NO3)2·6H2O, Fe(NO3)3·9H2O, urea and NH4F is 1-5:0.5-5:2-10:2-10.

4. The method for preparing a nanowire array composed of a cobalt-iron-based heterostructure according to claim 1, characterized in that: In S2, the temperature of the hydrothermal reaction is 100-200°C and the time is 4-12h.

5. The method for preparing a nanowire array composed of a cobalt-iron-based heterostructure according to claim 1, characterized in that: In S3, the heating and maintaining step has a heating rate of 3-10°C min -1 , heat to 200-500℃ and maintain for 1-10h.

6. The method for preparing a nanowire array composed of a cobalt-iron-based heterostructure according to claim 1, characterized in that: In S3, the concentration of the sodium sulfide solution is 0.01-0.1 mmol / mL.

7. The method for preparing a nanowire array composed of a cobalt-iron-based heterostructure according to claim 1, characterized in that: In S3, the temperature of the hydrothermal reaction is 100-200°C and the time is 2-12h.

8. A nanowire array composed of a cobalt-iron-based heterostructure, characterized in that: The method is described in any one of claims 1 to 7.

9. Use of the nanowire array composed of the cobalt-iron based heterostructure as claimed in claim 8 in preparing a working electrode for an oxygen evolution reaction catalyst.

Citation Information

Cited By

  • Preparation method of OER catalyst of cobalt-iron-doped Bi2O3 composite graphene oxide

    CN120026362A

  • Wheat-ear-shaped super-hydrophilic-super-aerophobic cobalt-iron-based electrocatalyst and application thereof

    CN121915452A